Does the Principle of Federalism in the Legislative Regulation of Administrative Liability Comply with the Constitution of the Russian Federation? - T. Z. Zokirov (Сибирское юридическое обозрение, 2025)
This article addresses the legitimacy of the principle of federalism within the institution of administrative liability. This principle is reflected in the distribution of powers and jurisdictions between the Russian Federation and its constituent entities concerning the establishment and enforcement of administrative liability measures. At the same time, the field of administrative legal science has raised legitimate concerns regarding the constitutional validity of this principle. The article presents various legal positions expressed by the highest courts of the Russian Federation, courts of general jurisdiction, and leading Russian scholars in administrative law on the matter. Several arguments are put forward in support of the constitutional legitimacy of federalism in the sphere of administrative liability. In particular, the article justifies the need to distinguish between the principles of federalism in the substantive and procedural aspects of administrative regulation. This distinction is necessary not only due to the fundamentally different content of each, but also because of the differing constitutional and legal foundations for their legitimacy. It is argued that the principle of federalism enjoys its most stable constitutional and legal footing in the procedural regulation of administrative liability – at least in the context of initiating administrative offense proceedings by officials of jurisdictional bodies in the constituent entities of the Russian Federation. The article further identifies certain inconsistencies in federal legislation, judicial practice, and administrative legal scholarship in the interpretation of the Constitutional Court's positions regarding the legitimacy of federalist principles in both the substantive and procedural domains of administrative liability. Conclusions are drawn regarding the recognition by the Constitutional Court of the Russian Federation of the legitimacy of the broad, competing competence shared by the Russian Federation and its constituent entities in the field of administrative regulation. Furthermore, the article points to the likely existence of matters of joint jurisdiction in this domain – even if not explicitly named in the Code of Administrative Offenses of the Russian Federation. Elements of such joint competence can be inferred through interpretation of Articles 1.3 and 1.3.1 of the Code.